IMPROVEMENT OF ACTIVITIES OF HOUSING AND UTILITIES IN THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2023)
Modern innovative development of society and economics reveals new, nontraditional directions of quality growth. One of the urgent ways to increase the efficiency of housing and communal services is the creation of "smart" cities and "smart" houses. Their implementation should be carried out progressively and on the basis of economic justifications